BASTBANPEM Application Stakeholders' Perceptions on Accountability and Transparency of the Ministry of Agriculture's Financial Reports - Nurvania, Regna; Syarief Hidayatulloh, Furqon; Koeswanda, Harry (Quantitative Economics and Management Studies, 2024)
The phenomenon that occurs is the achievement of a WTP Opinion by Financial Audit/BPK of Indonesian Republic in each preparation of Audited Financial Reports. However, there are still BPK-RI findings regarding Accountability for Government Research Assistance, which have been repeated until now. The Ministry of Agriculture has followed up on this by creating an Online BASTBANPEM Application. Therefore, it is interesting for the researchers to examine how financial report users perceive financial report accountability and transparency. Therefore, this research aims to find out the differences in perceptions between internal and external stakeholders regarding financial reporting using the BASTBANPEM application in the Ministry of Agriculture. The research method used descriptive quantitative methods, which are analyzed using the Non-Parametric Independent Sample Test. The finding that there are differences in perceptions between internal and external stakeholders on the Transparency variable. In the Accountability variable there are also differences in perception but they are not significant, namely only in the indicators of law & honesty and process. Based on this research result, it is expected that it can be used as material for evaluating the success of government assistance programs as well as making decisions and improvements needed in preparing financial reports and implementing future government assistance programs.